KEEFEKTIFAN METHOD DISCOVERY TERHADAP HASIL BELAJAR MENYUSUN TEKS ANEKDOT DILIHAT DARI TINGKAT KEMANDIRIAN TINGGI DAN RENDAH SISWA KELAS X DI SMA N I PECANGAAN - Nayla, Azzah (SASINDO, 2014)
A series of existing language learning method and is used by teachers inschools, discovery method is a method of learning that implement processes of selfdevelopment(self-development) that requires them to cultivate the mind. The aim ofthis research can be described as follows. 1) To determine mastery learning through theimplementation of discovery methods on material compiled anecdotes text seen froma high degree of independence and low class X of SMAN 1 Pecangaan. 2) To determinesignificant differences anecdotes learning outcomes compose text based on a highdegree of independence and low class X of SMAN 1 Pecangaan with discoverymethods. In this study, the research method used is quantitative qualitative researchmethods.Quantitative method is a method of data Qualitative research results in theform of numbers and how to analyze it using statistics which are then describedqualitatively. Data collection techniques in this study, namely through interviews,questionnaires (questionnaire), test and sampling. Analysis Instruments namely thevalidity of items, Reliability, Power Grain Problem differentiator, and level ofdifficulty. The preliminary analysis include, Test normality, Mean (average deviation),and the t test.Based on the research results, methods of discovery makes learning outcomesof students of high and low self-reliance has increased significantly. The use ofdiscovery method education for students a high degree of independence and selfreliancelower level students there is a difference. For students with high independenceof discovery methods were more effective than lower student independence.Based on the research that has analyzed it can be concluded that (1) discoverymethod effective on learning anecdotes compose text in both high and low classindependence, (2) there is a significant difference in the results with the ability tocompose text anecdotal discovery method students of high and low degree ofindependence. Based on this, the research suggested method of discovery should bebased on a number of considerations, including the purpose of learning, the teachersability to lead, the ability of students, number of students, the time available, andexisting facilities.Keywords: discovery methods, compiling anecdotes text, high and low degree ofindependence